[retracted] Peningkatan Pemahaman Perilaku Prososial melalui Layanan Informasi dengan Media Blog - Asroful Kadafi; Beny Dwi Pratama (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2016)
This study aimed to improve the understanding of the students’ pro-social behavior. This was a guidance and counseling action research with quantitative approach. The sample of this study was thirty students who were taken by using purposive sampling technique. The data collection method for this study was done through observation and employing psychological scale to find out the understanding of the students’ pro-social behavior.  The data analysis for this study was descriptive analysis by calculating the improvement percentage of pro-social behavior scale score on every given informational service action.  The result of this study showed that there was 85% improvement in the understanding of pro-social behavior after the informational service through Blog media was given. This study gives an alternative of the use of Blog media as a strategy for the counselor in improving the understanding of the students' pro-social behavior.